A theoretical contribution to the characterization of the electronic structure and spectroscopic properties of the low-lying states of strontium monoiodide, SrI. (July 2021) - de Melo, Gabriel Fernando; Ornellas, Fernando R.
Highlights: Reliable and accurate potential energy curves for Λ + S and Ω states of SrI. Most complete characterization of the states to date. Dipole and transition moments, Einstein Av´v´´ emission coefficients, and radiative lifetimes. Experimental investigation of the new A´ 2 Δ state should be significantly facilitated. Abstract: A high-level theoretical approach – SA-CASSCF/MRCI – is used to explore the electronic structure and spectroscopic properties of a manifold of low-lying electronic states of the radical strontium monoiodide, SrI. For both Λ + S and Ω representations, potential energy curves are constructed, and the associated spectroscopic parameters derived. Dipole moment functions and vibrationally averaged dipole moments allow one to quantify the polarity of the various states. With the transition dipole moment functions, Einstein Av'v'' coefficients for spontaneous emission were computed for pairs of selected states and radiative lifetimes evaluated for the low-lying vibrational levels of the excited electronic states. Reliable results are also provided for the yet unknown states A' 2 Δ and E 2 Σ + which can guide spectroscopists to their experimental detection. Combined with recent theoretical work on SrF, SrCl, and SrBr one now can have a broad perspective of the trends in spectroscopic properties of this series of halides. Graphical abstract: Image, graphical abstract